Psalm 104 en die Godsdienstradisies van Aten en Baal - Pistorius, H. G. (University of Pretoria, 2015)
Psalm 104 paints a picture of Yahweh dressed in the royal robes of both Aten and Baal. The variety of references to Ancient Near Eastern gods points to a rich and complicated history of the origins of Psalm 104, Israel and Israelite theology. The origins of Psalm 104 in all likelyhood include oral traditions, cultic contexts and years of redactional rearrangement and rewriting. Akhenaten used a centralised cult and monolatrism to achieve political stability in Egypt. Years later Hammurabi used Marduk as chief deity in Babylonia to centralise power and create political and religious stability in his kingdom. It is within this Ancient Near Eastern tradition of using religion and one specific deity to achieve political stability that Psalm 104 finds its origins and cultic context. The early Israelite monarchy finds itself amidst uncertain political circumstances. The early kings used a centralised monarchy and monolatrism to achieve economic and political stability. The early Israelite government also used other Egyptian influences including governing methods, policies and the use of Egyptian scribes. The monarchy used cultic personal to communicate politically sanctioned theology and contact between cultic personal and Egyptian scribes intertwined with a Canaanite heritage has a cosmopolitan and culturally diverse Psalm 104 at its end. The psalm is used as a war liturgy, with Chaoskampf-motifs to legitimise the Israelite king s military action and kingship. This is done by ritual re-enactment on cultic level connecting Yahweh s mythic action to that of the king s present conflict.
free